PENGGUNAAN REALIA LABEL HARGA ZEIKOMI (税込) DAN ZEINUKI (税抜) DALAM PEMAHAMAN LINTAS BUDAYA JEPANG-INDONESIA - Bertha Nursari (LINGUA : JURNAL ILMIAH, 2019)
In Japanese language teaching, either in Japan and outside Japan, the teachers are faced learners who have different cultures both in terms of mieru bunka (見える文化visible culture) and mienai bunka (見えない文化 invisible culture). As teachers who teach foreign languages ​​and learners who study foreign languages, both parties should not ignore culture that also appears in the learning process of foreign languages ​​(Yashiro, K & Sera, T., 2010). This paper will examine the use of zeikomi (税込 price include tax) and zeinuki (税抜price exclude tax) price label realia in terms Japanese-Indonesian intercultural understanding. The method which used in this paper is literary research. Some terms that appear in everyday life such as zeikomi (税込)、zeinuki (税抜き), B hin (B 品, B quality)、wake ari shouhin (分けあり商品 imperfect product) are used as vocabulary inputs in class activities. The term zeikomi, zeinuki, B hin and wake ari shouhin are examples of mienai bunka will provide intracutural understanding to learners. This paper shows that using realia can make classroom’s activities more interesting.